Optimizing Agricultural Mechanization to Enhance The Efficiency and Productivity of Farming In Indonesia: A Review - Wijayanto, Budi; Puspitojati, Endah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Agricultural mechanization has emerged as a cornerstone of modernizing the agricultural sector in Indonesia, playing a pivotal role in enhancing productivity and efficiency. The growing population and the necessity for increased agricultural output have driven the adoption of mechanization to overcome challenges such as labor shortages and the adverse effects of climate anomalies. The introduction of agricultural equipment follows a selective principle by considering the local area's socioeconomic conditions. Future agricultural mechanization utilizes technologies based on weather analysis, soil sensor information, and satellite and drone imaging that can increase agricultural productivity. Precision agriculture innovation to improve the accuracy of farm business management is carried out by utilizing sensor systems, drones, remote sensing, digital technology, and the Internet of Things (IoT) to collect, process, and present data that smart farming systems will use. Integrated information system innovations for the supply chain are designed to bridge farmers, distributors, markets, and end buyers by utilizing mobile applications. The traditional to modern transition process and the implementation of smart digital farming require mentoring and field learning in the agricultural process from upstream to downstream. This review provides a comprehensive overview of the development, challenges, opportunities, and prospects of agricultural mechanization in Indonesia, offering insights into how these efforts can support the country's economic growth and food security. Materials were prepared from various sources, including development planning documentation program reports, evaluation, and critical analysis of different research results.